METHODOLOGY FOR CREATING AND TEACHING MODELING OF KINEMATIC PHENOMENA IN AN ANILOGIC ENVIRONMENT (Scientific journal of the Fergana State University, 2025)
The article discusses scientific and methodological research solutions for modeling kinematic phenomena of a physics course using AnyLogic software. Their capabilities are also based on the Ontological Equipment used to create the modeling of kinematic modeling phenomena. The model modeling of kinematic phenomena created in the AnyLogic environment is demonstrated visually and research in the field of methods of use in the educational process is presented.